THE FACTORS ASSOCIATED WITH THE IMPLEMENTATION OF COVID-19 VACCINE 3 AT PUBLIC HEALTH CENTER IN OGAN KOMERING ULU DISTRICT - Aprilianti Putri; Eka Joni Yansyah; Sabtian Sarwoko; Fera Novitry (Indonesia Epidemiological Journal, 2023)
ABSTRACT Background: A new type of Corona virus (Covid-19), also called Severe Acute Respiratory Syndrome Corona Virus 2, was discovered in humans in Wuhan, China. Covid-19 vaccination can form herd immunity in society, thereby reducing morbidity and death rates due to Covid-19. This researcher aims to determine the analysis of factors related to the implementation of the COVID-19 vaccine in Sukanegeri Village, the UPTD Working Area of the Betung Community Health Center, East Oku Regency, in 2023. Method: This research design uses analytical observation with a cross-sectional approach. The sample was taken from the total population, namely all people who had received the 2nd COVID-19 vaccine in Sukanegeri village, the UPTD Working Area of the Betung Community Health Center, East Oku Regency, totaling 1,554 people, so the sample size was 90.47 (rounded to 91) respondents. The statistical test used is the chi-square test. Results: The results of the bivariate analysis show that, there is a significant relationship between education and the implementation of the 3 covid-19 vaccine with a p value of 0.000, there is a significant relationship between knowledge and the implementation of the 3 covid-19 vaccine with a p value of 0.000, there is a significant relationship between attitude with the implementation of the 3 covid-19 vaccine with a p value of 0.000, there is a significant relationship between the availability of information and the implementation of the 3 covid-19 vaccine with a p value of 0.001, there is a significant relationship between family support and the implementation of the 3 covid-19 vaccine with a p value of 0.001. Conclusion: There is a significant relationship between education, knowledge, attitudes, availability of information, and family support for the COVID-19 vaccine.